The origins of the British invasion of Iraq in 1918: A historical study - Mijbil, Qatran Abbas (Al-Adab Journal, 2021)
Britain worked before the military occupation of Iraq to extend its roots inside Iraq by following several methods and methods. The foremost of these methods were the operations of proselytizing and establishing banks، which made them by petitioning Iraq and the Iraqis، which facilitated the occupation process. The issue of its delay in the process of completing the occupation for four years indicates the violent resistance it witnessed during its military operations، as well as the Ottoman forces were able to besiege the British general (TOWSEND) with his forces for a period of five months until he was forced to surrender in 1916، but a new British campaign reached Iraq from India. She succeeded in inflicting defeat on the Ottoman army and occupying the city of Mosul in 1918 A.D.، and Britain published a statement at the end of the war، announcing that its goal in fighting the Arabs with the Ottomans was to liberate the Arabs from Ottoman control. They found that the major countries are heading to the status of Iraq، but the British mandate، and this means the continuation of foreign control and the absence of independent national rule.